Implementation of Digital Signatures in the Integrated Patient Progress Notes System at XYZ Hospital Bandung - Supriadi, Tasya Saldira Putri; Syahidin, Yuda; Yunengsih, Yuyun (International Journal Software Engineering and Computer Science (IJSECS), 2024)
This study aims to implement a digital signature system for filling out Integrated Patient Progress Notes (CPPT) using QR-Code technology. The research method employed is the waterfall development model. The stages of the study include requirements analysis, data collection from various sources, system design, implementation according to the design, testing, and reporting. The study was conducted at XYZ Hospital in Bandung, where it was found that the CPPT signing process is still manually done using a pen, which is considered inefficient as it takes a long time for authorization and is prone to manipulation, thereby reducing the document's validity. The implementation of a digital signature aims to simplify the document signing process quickly without the need for printing, sending, or waiting for physical documents, allowing it to be done digitally and automatically, thereby increasing speed and efficiency. This system also provides authentication assurance by the rightful owner, ensures document security, reduces the risk of damage or loss, and minimizes the possibility of manipulation, thus providing convenience for staff and doctors in terms of time and data accuracy.